2017
DOI: 10.1021/acs.jctc.6b01108
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Energy Relaxation in Pump–Probe Vibrational Spectroscopy of Hydrogen-Bonded Liquids

Abstract: We introduce a non-equilibrium molecular dynamics simulation approach, based on the generalized Langevin equation, to study vibrational energy relaxation in pump-probe spectroscopy. A colored noise thermostat is used to selectively excite a set of vibrational modes, leaving the other modes nearly unperturbed, to mimic the effect of a monochromatic laser pump. Energy relaxation is probed by analyzing the evolution of the system after excitation in the microcanonical ensemble, thus providing direct information a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 54 publications
1
40
0
Order By: Relevance
“…Further insight into the character of the crystal dynamics in more realistic systems is obtained from the results of MDS in and out of equilibrium within a 3 ×3×2 pentacene crystal cell of the same polymorph. Out-of-equilibrium MDS were obtained from microcanonical dynamics following a thermalization by a hotspot thermostat ( 39 ) centered at 1 THz. A connection to the FED experiments can be obtained by simulating diffraction patterns for each MDS snapshot ( 37 , 40 ), as illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Further insight into the character of the crystal dynamics in more realistic systems is obtained from the results of MDS in and out of equilibrium within a 3 ×3×2 pentacene crystal cell of the same polymorph. Out-of-equilibrium MDS were obtained from microcanonical dynamics following a thermalization by a hotspot thermostat ( 39 ) centered at 1 THz. A connection to the FED experiments can be obtained by simulating diffraction patterns for each MDS snapshot ( 37 , 40 ), as illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly in solution, while solvent induced effects could be estimated using force field MD simulations, 56 typically direct energy transfer can occur on the same timescale of about 10 ps, [57][58][59][60] so it is difficult to disentangle from solvent-mediated IVR, which can occur on the timescale of about 1 ps. 54,[61][62][63][64][65] The reported results provide fundamental understanding of energy transfer that may limit the effectiveness of catalysts mounted on metals.…”
Section: System A'(1) A''/a'(2)mentioning
confidence: 99%
“…The net result is a few vibrations at higher temperature than the rest of the system, which is precisely what is needed to study VET from MD. Dettori et al 70,71 have demonstrated these methods for a pumpprobe style simulation of hydrogen-bonded liquids and here we follow a similar protocol to selectively target vibrations of interest. Each of these GLE pumped vibrations emulate a Gaussian centered pump of width 33 cm -1 , which act on a 3 × 3 × 3 super-cell of RDX for 10 ps to establish a non-equipartition of vibrational kinetic energy; the pump is subsequently removed and spectra are collected in the micro-canonical ensemble.…”
Section: B Computationalmentioning
confidence: 99%